BENTUK BULLYING YANG DIALAMI SANTRI DAN UPAYA PENCEGAHAN: (Studi Kasus MTs Jeumala Amal Pidie Jaya) - Fakhrizal, Fakhrizal; Dahri, Dahri; Salami, Salami; Zulfatmi, Zulfatmi (Desultanah: Journal Education and Social Science, 2023)
This study aims to describe the forms of bullying experienced by students and prevention efforts. The research method was conducted with a case study located at MTs Dayah Jeumala Amal. The research data was obtained through 9. informants consisting of BK teachers, 6 homeroom teacher and 2 Students. Interview techniques are used to obtain data and analyzed in a qualitative descriptive manner. The results of the study found forms of bullying that occurred in MTs Dayah Jeumala Amal that are still experienced by students, namely; 1) physical bullying in the form of lightly hitting, 2) verbal bullying in the form of mocking, and 3) social bullying in the form of social distancing. Prevention efforts are carried out through giving advice, warning gradually, communication with parents/guardians of students, and socializing continuously. The implication has an impact on the lack of bullying that occurs in Islamic boarding schools.